Japanese and Western Influences on the Local Animation Character Design Identity in Malaysia - Faryna Mohd Khalis; Syazliyati Ibrahim; Shafilla Subri; Nurul Atikah Adnan; Abdullah Kula Ismail (Journal of Visual Art and Design, 2023)
Identity is regulated by culture and can be delivered meaningfully in numerous expressions, among which animated designs. In tandem with technological evolution, animation today shows fusions of various cultures. Two main influences in the Malaysian animation industry are Japan and Western countries due to their status as pioneers in animation. Therefore, this study aimed to examine the influence of Malaysian, Japanese and Western animated character designs on the local university students’ production of their character designs. This study was conducted based on semiotic theory, followed by a research method that employed a content analysis approach using the SPSS software. Through the analysis of cross-distribution and Chi-Square, it was found that the criteria of physique, national characteristics, and colors in the students’ work showed similar characteristics to both local and foreign animations. Consequently, further studies should be conducted to comprehend why the students are inspired by Japanese and Western styles. These influences also raise the question of whether these cross-cultural forms lead to a new identity of Malaysian animation or only a trend.